Development and validation of an LC–MS/MS method for the simultaneous quantification of milbemycin oxime and praziquantel in plasma: application to a pharmacokinetic study in cats - Xie, Shiting; Lu, Yixing; Wang, Jun; Lin, Changcheng; Ye, Peiyu; Liu, Xiaolin; Xiong, Wenguang; Zeng, Zhenling; Zeng, Dongping (Frontiers in Veterinary Science, 2023)
Milbemycin oxime (MBO) and praziquantel (PZQ) have a broad spectrum of biological activity and are commonly used to treat the parasitic infection in the veterinary clinic. In this study, a fast and efficient LC-MS/MS method was established and validated for the simultaneous determination of MBO, PZQ, cis-4-hydroxylated-PZQ (C-4-OH-PZQ) and trans-4-hydroxylated-PZQ (T-4-OH-PZQ) and in cat plasma.Extraction of analytes and internal standards from cat plasma by acetonitrile protein precipitation, allows rapid processing of large batches of samples. MBO, PZQ, C-4-OH-PZQ, T-4-OH-PZQ, and internal standard (IS) were eluted for 13.5 min on a C18 column with a 0.1% formic acid water/acetonitrile mixture as the mobile phase. Results showed that the method had good precision, accuracy, recovery, and linearity.The linearity range was 2.5-250 ng/mL for MBO, and 10-1000 ng/mL for PZQ, C-4-OH-PZQ, and T-4-OH-PZQ. The intra-day and inter-day precision CV values of the tested components were within 15%.The extraction recoveries of the four components ranged from 98.09% to 107.46%. The analytes in plasma remained stable for 6 h at room temperature, 26 h in the autosampler (4 °C ), after freeze-thaw (−20 °C ) cycles, and 60 days in a −20 °C freezer.